2014
DOI: 10.3892/ol.2014.1913
|View full text |Cite
|
Sign up to set email alerts
|

Removal of an intra-abdominal desmoplastic small round cell tumor by repetitive debulking surgery: A case report and literature review

Abstract: In the current study, a case of recurrent desmoplastic small round cell tumor (DSRCT) is presented, which was successfully treated by repetitive debulking surgery. In May 2010, a 39-year-old male, with a history of surgical resection of intra-abdominal DSRCT, visited the Ibaraki Medical Center, Tokyo Medical University Hospital (Ami, Japan) with severe lower abdominal discomfort. Abdominal computed tomography revealed a large tumor in the pouch of Douglas with a small number of nodules in the abdominal cavity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This suggested that effective cytoreduction and R0 resection would be beneficial to early-stage patients with no distant metastasis. [ 26 , 27 ] Some researchers [ 28 , 29 ] have also found that a combination of neoadjuvant chemotherapy and surgery not only brings patients an opportunity of radical surgery, it is also of certain significance for patients who can tolerate secondary surgery by adopting high-intensity radiochemotherapy combined with bone marrow transplantation. Li Gang et al [ 4 ] reviewed 5 patients with DSRCT primarily occurred in the chest.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that effective cytoreduction and R0 resection would be beneficial to early-stage patients with no distant metastasis. [ 26 , 27 ] Some researchers [ 28 , 29 ] have also found that a combination of neoadjuvant chemotherapy and surgery not only brings patients an opportunity of radical surgery, it is also of certain significance for patients who can tolerate secondary surgery by adopting high-intensity radiochemotherapy combined with bone marrow transplantation. Li Gang et al [ 4 ] reviewed 5 patients with DSRCT primarily occurred in the chest.…”
Section: Discussionmentioning
confidence: 99%